The tetrapeptide Ac-SDKP and angiotensin converting enzyme in tuberculous pericarditis and fibrosis - Ramasamy, Vinasha (Department of Integrative Biomedical Sciences (IBMS), 2021)
Tuberculous pericarditis is an extra pulmonary form of tuberculosis (TB) which leads to a lifethreatening form of pericardial fibrosis in up to 25% of patients despite anti tuberculous therapy. The mechanisms leading to the fibrotic phenotype following infection are poorly understood. A proof of concept study revealed decreased levels of the antifibrotic N-acetylseryl-aspartyl-lysyl-proline or Ac-SDKP in tuberculous pericardial fluid as compared to control (non infectious) pericardial fluid. Ac-SDKP is a physiological peptide that is synthesised from its precursor protein thymosin β4 by the sequential action of meprin-α and prolyl oligopeptidase (POP) and is cleaved by angiotensin-1 converting enzyme (ACE). Importantly, a role of ACE and Ac-SDKP in the regulation of inflammation and fibrosis in multiple tissues and organs has been increasingly described in the literature. This has prompted interest in both the mechanisms of and potential for protective benefits of ACE inhibitors and Ac-SDKP analogue administration in fibrotic disease. The aim of this project was to investigate a) the molecular mechanisms of the antifibrotic effects of Ac-SDKP in the development of fibrosis, particularly in TB pericarditis, and b) the potential of ACEi and Ac-SDKP analogues in vitro in fibrosis prevention. Pericardial fluid and blood samples from patients with TB pericarditis or undergoing coronary artery bypass surgery (non-infectious controls) was used to investigate the metabolism of AcSDKP in the tuberculous pericardium. Ac-SDKP levels as measured by ELISA, were significantly decreased (2.3 fold) in TB pericardial fluid as compared to controls. This reduction in Ac-SDKP levels was accompanied by a local 28% increase in the enzymatic activity of ACE, but no change in POP enzyme activity levels, both of which were measured using fluorogenic assays. This suggests that an increase in ACE activity in the pericardium following infection by the mycobacterium leads to a reduction of the levels of the antifibrotic peptide which is likely to contribute to the pathophysiology of fibrosing pericarditis. A mass spectrometric (MS) approach was employed in order to identify proteins whose expression is modulated by the effect of Ac-SDKP in the proteome and secretome of a human lung fibroblast cell line (WI-38). Label free quantitative MS was employed to identify 114 and 44 differentially expressed proteins in Ac-SDKP fibroblast proteome and secretome respectively. Various extracellular matrix components and their related factors such as collagens, cytoskeletal proteins and inflammatory proteins, were identified among the differentially regulated proteins. Reactome pathway analysis confirmed the significant enrichment of Ac-SDKP-related extracellular matrix proteoglycans and extracellular matrix in the differentially expressed proteins of the secretome. Using the same cell line, the antifibrotic effects of Ac-SDKP analogues and ACE inhibitors were investigated through quantitative western blotting for transforming growth factor β (TGF-β) and Smad 3 levels, and using a hydroxyproline assay. Ac-SDKP prevented TGF-β and collagen expression through inhibition of Smad 3 phosphorylation. The Ac-SDψKP analogue (whereby the peptide bond between the aspartate and lysine is reduced) alone prevented TGF-β mediated collagen secretion. The combination of Ac-SDKP and the N domain-selective inhibitor RXP407, but not the non-selective lisinopril had an additive effect on the inhibition of collagen in fibroblasts. However, the antifibrotic effect of Ac-SDψKP was comparable to the combination of Ac-SDKP and RXP407 and was not improved with added ACE inhibition. Finally, the ACE signalling response to Ac-SDKP and the ACE inhibitors RXP407 and lisinopril was investigated using mass spectrometry and quantitative western blotting for phospho JNK and JNK. The ACE inhibitors as well as Ac-SDKP triggered the ACE signalling cascade to induce JNK phosphorylation. This highlights a potential new mechanism for the anti-inflammatory and antifibrotic effects of Ac-SDKP and the inhibitors. This thesis has demonstrated an altered metabolism of Ac-SDKP is associated with increased ACE activity in the tuberculous pericardium. It has also provided a deeper understanding of the antifibrotic action of the tetrapeptide, and in vitro evidence for the use of the analogue AcSDψKP and inhibtion of N domain catalytic activity for decreasing fibrosis. These findings form a solid basis for future in vivo pharmacological studies on the effects of Ac-SDKP analogues and ACE inhibitors in the prevention and management of fibrotic conditions. Importantly, these therapeutic options present an exciting avenue to follow in the prevention of fibrosing pericarditis in TB pericarditis.